2022
DOI: 10.26418/elkha.v14i1.49910
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Potential of Solar Energy PT PJB UP Muara Karang Rooftop Area Using HelioScope

Abstract: Year after year, there has been a rise in use of electrical power. The industrial, home, commercial, and public sectors accounted for 234,617.88 GWh of PLN's electrical energy sales in 2018. Meanwhile, the household, industrial, commercial, social sector, government office buildings, and public street lighting consumed 2,857.06 GWh of electrical energy in DKI Jakarta. The majority of the energy resources required by interconnected networks are fossil (coal). As a result, a future alternative to fossil fuels is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…When considering a building's rooftop potential, these factors certainly influence the ability of sunshine to fall on the roof's surface. The same research done by Samsurizal et al (2022) has shown the use of HelioScope connected to Google Earth applications as it can accurately calculate the selected building roof area for solar replacement. After drawing the roof layout in the default imagery map, HelioScope automatically calculates the number of solar modules that need installation and the orientation of the PV modules.…”
Section: )mentioning
confidence: 96%
See 2 more Smart Citations
“…When considering a building's rooftop potential, these factors certainly influence the ability of sunshine to fall on the roof's surface. The same research done by Samsurizal et al (2022) has shown the use of HelioScope connected to Google Earth applications as it can accurately calculate the selected building roof area for solar replacement. After drawing the roof layout in the default imagery map, HelioScope automatically calculates the number of solar modules that need installation and the orientation of the PV modules.…”
Section: )mentioning
confidence: 96%
“…For this most studies have relied on HelioScope which as it is a potential solar radiation simulation web tool The HelioScope application was used to estimate the potential of solar energy on rooftops. Samsurizal et al (2022) have split the research into four sections to explain the methodology of using the HelioScope application to accurately estimate solar potential The research done by Samsurizal et al (2022), indicated that the designers need to assess the selected buildings surrounding environment and collect building data for the examination. The necessary data for the study includes height of the building, location, building type, surrounding building height.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Energi listrik yang dikeluarkan oleh modul surya tidak hanya bergantung pada besarnya intensitas iradiasi matahari yang terpapar pada modul surya, dimana kenaikan temperatur pada permukaan modul surya dapat memiliki potensi untuk menurunkan kemampuan modul surya dalam menghasilkan energi listrik (Andi Makkulau et al, 2019) (A . Untuk meningkatkan kemampuan modul surya, diperlukan optimalisasi sehingga daya keluaran dari modul surya dapat ditingkatkan (Samsurizal, Afrianda & Makkulau, 2022). Nilai intensitas matahari atau nilai radiasi matahari yang tersimpan dalam panel surya.…”
Section: Pendahuluanunclassified
“…13 of 2019, and Ministerial Regulation No. 16 of 2019, regarding the use of Roof Solar Power Generation Systems by customers of the State Electricity Company (PLN). These policies provide more business opportunities and flexibility for the renewable energy sector to flourish.…”
Section: Introductionmentioning
confidence: 99%